PEMANFAATAN AIR BEKAS WUDHU UNTUK BUDIDAYA TANAMAN OBAT DI KEBUN AGROWISATA RELIGI PADANGLAMPE - Boceng, Annas; Nontji, Maimuna; Coneng, Amir (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2022)
This community service activity aims to utilize water used for ablution from the Darul Mukhlisin mosque congregation, which is located ± 100 m from the medicinal plant garden, by collecting the water in a reservoir and draining it into the medicinal plant garden. This activity was carried out with partners from the Darul Mukhlisin farmer group and the local community. The stages of the activities carried out were: (1). Preparation of tools and materials (2) Making a reservoir with a size of 200 cm x 100 cm x 120 cm., (3) Making a water pipe installation from the reservoir to a water tank with a size of ± 100 m, , (4) Installing a water tank and water pump. The output targets that have been obtained are the availability of water reservoirs used for ablution, installation of water pipes complete with water pumps that are installed from the location of the ablution place to the medicinal plant garden area